PS01.235: THE METHOD AND THE SHORT OUTCOME OF MEDIASTINAL LYMPH NODES DISSECTION FOR ESOPHAGEAL CANCER USING A TRANS-BICERVICAL AND TRANSHIATAL APPROACH UNDER THE PNEUMOMEDIASTINUM. (14th September 2018) - Tokairin, Yutaka; Nakajima, Yasuaki; Kawada, Kenro; Hoshino, Akihiro; Okada, Takuya; Ryotokuji, Tairo; Okuda, Masafumi; Kume, Yuichiro; Kawamura, Yudai; Yamaguchi, Kazuya; Nagai, Kagami; Akiata, Keiichi; et al.
Abstract: Background: We previously reported the performance of mediastinoscopic esophagectomy with lymph node dissection (MELD) under pneumomediastinum using a transcervical and transhiatal approach as a method of radical esophagectomy. For more complete lymph node dissection, it is necessary to dissect via not only left cervical but also right cervical approach in pneumomediastinum. We herein report the dissection method for upper mediastinum using a cervico-pneumomediastinal approach including right cervical approach in pneumomediastinum and the short surgical outcome. Methods: This method was applied to nine cases for esophageal cancer. The right recurrent nerve was first identified using an open approach. Pneumomediastinum was then initiated to allow for the 105 and 106recR lymph nodes to be completely dissected along the right mediastinal pleura, the right vagus nerve, the proximal portion of the azygos vein and the right bronchial artery. The left recurrent nerve (106recL) lymph nodes and 106tbL lymph nodes were dissected using a cross-over technique, as described previously. Results: This operation using bilateral cervical approach in pneumomediastinum were performed for nine cases. The median operation time and bleeding is 606 minutes and 506 ml, respectively. The median post-operative stay is 15 days. Conclusion: MELD is therefore considered to be a more minimally invasive and useful modality for radical esophagectomy than the thoracic approach, although the field of view is different from that of the thoracic approach. Disclosure: All authors have declared no conflicts of interest.